The development of the concept of friends of young children at the UP Child Development Center (2007)
This study aimed to determine young children's concept of friends. Thirty children whose ages range from 3 years to 5 years old as of Academic Year 2005-06 were randomly selected from the University of the Philippines Child Development Center (UP CDC) to participate in the study. In a one-on-one interview, each child was asked why a peer is considered "a friend" or a "non-friend"; and how he feels when he is with them. The children's responses were tabulated and analyzed for recurring themes and patterns. Results suggest that preschoolers' concept of friends highlights play, togetherness and liking. Cognitive development and emotional experience that come with age appear to be a contributing factor to the difference in the children's conceptions. Seemingly, their ability to characterize a friend and a non-friend, and their capacity to label and express their emotion are developed with age. Observed as well are some differences between the responses of boys and girls but such variation cannot be attributed to sex per se.
Keywords: Friendship in children; Interpersonal relationship in children